Low-dosage ozonation in gas-phase biofilter promotes community diversity and robustness - Yeung, Marvin (Microbiome, 2021)
BACKGROUND: The ozonation of biofilters is known to alleviate clogging and pressure drop issues while maintaining removal performances in biofiltration systems treating gaseous volatile organic compounds (VOCs). The effects of ozone on the biofilter microbiome in terms of biodiversity, community structure, metabolic abilities, and dominant taxa correlated with performance remain largely unknown. METHODS: This study investigated two biofilters treating high-concentration toluene operating in parallel, with one acting as control and the other exposed to low-dosage (200 mg/m(3)) ozonation. The microbial community diversity, metabolic rates of different carbon sources, functional predictions, and microbial co-occurrence networks of both communities were examined. RESULTS: Consistently higher biodiversity of over 30% was observed in the microbiome after ozonation, with increased overall metabolic abilities for amino acids and carboxylic acids. The relative abundance of species with reported stress-tolerant and biofilm-forming abilities significantly increased, with a consortium of changes in predicted biological pathways, including shifts in degradation pathways of intermediate compounds, while the correlation of top ASVs and genus with performance indicators showed diversifications in microbiota responsible for toluene degradation. A co-occurrence network of the community showed a decrease in average path distance and average betweenness with ozonation. CONCLUSION: Major degrading species highly correlated with performance shifted after ozonation. Increases in microbial biodiversity, coupled with improvements in metabolizing performances of multiple carbon sources including organic acids could explain the consistent performance commonly seen in the ozonation of biofilters despite the decrease in biomass, while avoiding acid buildup in long-term operation. The increased presence of stress-tolerant microbes in the microbiome coupled with the decentralization of the co-occurrence network suggest that ozonation could not only ameliorate clogging issues but also provide a microbiome more robust to loading shock seen in full-scale biofilters. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s40168-020-00944-4.